Calcineurin inhibitors or cyclophosphamide in the treatment of membranous nephropathy superimposed with FSGS lesions: a retrospective study from China - Hong-Guang He; Yi-Yun Huang; Qin-Qing Liang; Qiu-Rong Ye; An-Dong Li; Kun Ye; Qiu-Xia Wu; Yan-Wu You (Renal Failure, 2023)
Background Cyclophosphamide (CTX) and calcineurin inhibitors (CNIs) based regimens are recommended as immunosuppressive therapies for patients with idiopathic membranous nephropathy (IMN). Focal and segmental glomerular sclerosis (FSGS) lesions, which are common in membranous nephropathy (MN), are poor predictors of outcome. This study compared the differences of prognosis between two regimens in patients with IMN combined with FSGS lesions.Methods This retrospective study enrolled 108 patients with biopsy-proven IMN, accompanied with FSGS lesions, nephrotic syndrome and an estimated glomerular filtration rate (eGFR)≥60 mL/min/1.73 m2 who were treated with CTX or CNIs. We used propensity score matching (PSM) for balancing the confounding variables.Results During follow-up, 10 patients (10/55 [18.2%]; nine males) in the CNIs group showed a 50% decline in eGFR; eight had a not otherwise specified variant. Patients initially treated with CNIs had a significantly higher risk of progression to the primary outcome and a lower probability of complete or total remission. The relapse rate was higher in patients who initially received CNIs- than in those who received CTX-based treatment. Before PSM, age and 24-h urine protein level differed significantly between the groups. The PSM model included data from 72 patients. Worse outcomes were also noted among patients who initially received CNIs than those who received CTX-based treatments after matching.Conclusions Patients with MN combined with FSGS lesions have a higher risk of renal functional decline and a higher rate of relapse after CNIs than after CTX therapy.